Analisis Strategi Pemasaran Kopi Keliling Merek Briling di Kota Palangka Raya - Susilowati Widyaningsih; Fendy Hariatama; Grace Evelina Buji (Universitas Pendidikan Ganesha, 2026)
This study aimed to analyse the marketing strategy of the mobile coffee brand Briling in Palangka Raya using the Segmenting, Targeting, and Positioning (STP) approach. The research used a descriptive qualitative method and was carried out for three months. Data were collected through in-depth interviews, participatory observation, and documentation. The informants included the business owner, several employees, and consumers, supported by operational records from 24 mobile cart locations. The findings show that Briling’s market segmentation includes young adults aged 20–35, urban areas with high mobility, practical lifestyles, and purchasing patterns that occur during peak hours. The target market focuses on university students and young office workers, as this segment is large, growing, cost-efficient to reach, and suitable for the business’s capacity. Briling is positioned as a practical and accessible mobile coffee provider with a consistent taste, affordable prices, and modern cart designs. The application of the STP strategy proves effective. It helps Briling retain loyal customers, attract new buyers, and strengthen its competitive advantage among mobile coffee businesses.